Perancangan Model Pengambilan Keputusan Pemilihan Pemasok di Perusahaan Manufaktur Produk Farmasi dengan Pendekatan ANP BOCR - Anggy Fitria Sari; Gendut Suprayitno (Universitas Mercu Buana, 2020)
In the industry especially pharmaceutical, supplier selection process is a strategic issueand important because of supplier selection is a strategic activity, especially if thesupplier will supply critical items and / or will be used in the long term. To overcomethese problems, then the purpose of this study is to select proper supplier based on thespecified criteria so that the risk of error of supplier selection can be minimized. Basedon the results of supplier selection priority data using Analytic Network Process -Opportunity Cost Benefit Risk (ANP-BOCR) method obtained the criteria of advances insupplier technology have the greatest realistic value and the supplier A is the supplierthat have the greatest realistic weight and most deserve to be supplier of raw material(sodium chloride) for companies.